A novel germline HAVCR2 (TIM-3) compound heterozygous mutation is related to hemophagocytic lymphohistiocytic syndrome in EBV-positive peripheral T-cell lymphoma (NOS) with down-regulated TIM-3 signaling - Zhang, Yang; Wang, Zhihua; Hu, Guoyu; Li, Jieping; Chen, Yongheng; Jiang, Yi; Zhong, Haiying; Liu, Xianling; Hu, Chunhong; Peng, Honglin; Xu, Yunxiao; Cheng, Zhao; et al. (Frontiers in Oncology, 2022)
Recently,it have been reported that Hepatitis A Virus-Cellular Receptor 2(HAVCR2,encoding T-cell immunoglobulin and Mucin-Containing Protein 3[TIM3]) mutations are associated with severe hemophagocytic syndrome(HLH) in subcutaneous panniculitis-like T-cell lymphoma(SPTCL),and there are also frequent mutations in sporadic SPTCL,suggesting the individuals harboring HAVCR2(TIM-3) germline mutations are highly susceptible to familial or sporadic SPTCL .Here, we identify a novel germline compound heterozygous mutation of TIM-3 gene ,c.245A﹥G (p.Tyr82Cys) and c.265C﹥T(p.Arg89Cys) variations in a single familial case with EBV-positive peripheral T-cell lymphoma(NOS),accompanied HLH ;we also detected Tyr82Cys germline mutation in TIM-3 gene in one sporadic patient with cutaneous T cell lymphoma.We screened the distributive frequencies for TIM-3 mutations in healthy controls(n=87), B-(n=79) or T-cell lymphoma(n=25) not SPTCL, and the results showed that the mutation was found in two out of 25 patients with T-cell lymphoma but was not detected in 79 patients with B-cell lymphoma nor in a group of 87 controls. The mRNA expression of TIM-3 on primary cells and transfected HEK293 cells reduced significantly, indicating Tyr82Cys and Arg89Cys mutations is a loss-of function mutations on TIM-3,resulting in a weakened TIM-3 signaling.Our results suggest Tyr82Cys TIM-3 germline mutations are not only limited in SPTCL,and also occured in other types of T-cell lymphoma,especially complicated HLH. TIM-3 mutations may be an predisposing factor for T-cell lymphoma and molecular marker for auxiliary diagnosis in T cell lymphoma ,especially complicated with HLH.